Increased expression of advanced glycation endproducts in the gingival crevicular fluid compromises periodontal status in cigarette-smokers and waterpipe users - Dena Ali; Fatemah AlAhmari; Toshinari Mikami; Jagan Kumar Baskaradoss (BMC, 2022)
Abstract Background The aim was to assess the association between levels of advanced glycation endproducts (AGEs) in the gingival crevicular fluid (GCF) and periodontal parameters among cigarette-smokers and waterpipe-users. Methods Self-reported cigarette-smokers; waterpipe-users and never-smokers were included. Demographic data was recorded using a questionnaire. Periodontal parameters (plaque index [PI], gingival index [GI], clinical attachment loss [AL], probing depth [PD], and marginal bone loss [MBL]) were assessed in all groups. The GCF samples were collected using standard techniques and assessed for AGEs levels using enzyme-linked immunosorbent assay. Sample-size estimation was done and group-comparisons were done. Correlation between levels of GCF AGEs levels and periodontal parameters was assessed using a logistic regression model. Level of significance was set at P < 0.01. Results Eighty-two individuals (28 cigarette-smokers, 28 waterpipe-users and 26 never-smokers) were included. There was no difference in mean ages of all patients. Cigarette-smokers had a smoking history of 5.1 ± 0.2 pack years and waterpipe-users were using waterpipe for 4.4 ± 0.6 years. There was no statistically significant difference in PI, GI, clinical AL, PD and MBL in all groups. Levels of AGEs were significantly higher among cigarette-smokers (P < 0.001) and waterpipe-users (P < 0.001) than never-smokers. There was no significant correlation between levels of GCF AGEs levels and periodontal parameters in all groups. Conclusion Clinical periodontal status of individuals with a short history of cigarette-smoking and waterpipe-usage may appear similar to never-smokers. On a molecular level, cigarette-smoking and waterpipe-users express raised levels of AGEs than never-smokers that sirens about the ongoing yet latent periodontal inflammatory process.